Governing economies in areas of limited statehood: Anthropological perspectives - Jacob Rasmussen; Kirstine Strøh Varming (Danish Institute for International Studies (DIIS), 2016)
This DIIS-GOVSEA working paper reviews key debates within economic anthropology and related academic disciplines explaining how economic life is governed in areas of limited statehood. The paper briefly introduces some of the origins of economic anthropology before going into deeper discussions of a number of key debates within the field. The literature review and discussion is organised on the basis of six major themes that shed light on this research question: 1) embeddedness and economic transformations, 2) property governance, 3) informal and popular economies, 4) debt and money, 5) borders and cross-border trade, and 6) authority, governance and economic regulation. These themes are supported by case examples from the Somali territories in the East and Horn of Africa. Through the reviewed literature, the paper critically engages common categories, such as formal/informal, state/non-state, rational/moral, in order to provide insights for the study of economic behaviour and economic governance in areas of limited statehood.
Keywords: 330